(3cTa GdcTGas - (3SQGL GdOjf CHh MaU YeQ Hf YHO GdQMef Hf YeQ GdbRhjfj, YeQ GdbRhjfj,J (B745 (3g` s
(3ChdgG (B:s
q[(3Chdg ShQI GdESQGA(B]: (3bhdg (B(((3SHMGf(B)) (3Yde ddJSHjM s
(3BNQgG (B:s
(3Je gPG GdcJGH GdeHGQc HMeO Gddgq s
(3GdLRA GdKGfj HQbe (B149 (3chjJs
(3HgG fXGe GdJYbjHIs
(3hQOJ fSHJg Ydi UaMI GdZdGa Edi YeQ GdHjVGhis
(3JHUQI GdYfhGf (B:s
(3JMTjI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs